Costs of health and social services use in children of parents with mental illness - Tamara Waldmann; Maja Stiawa; Ümügülsüm Dinc; Gülsah Saglam; Mareike Busmann; Anne Daubmann; Bonnie Adema; Karl Wegscheider; Silke Wiegand-Grefe; Reinhold Kilian (BMC, 2021)
Abstract Background Children of parents with mental illness have a higher risk of developing mental health problems when compared with the general population. Therefore, families with parents with mental illness are a suitable target group for selective prevention. In order to plan and evaluate the health economic consequences of preventive interventions for this target group, data on the societal costs related to parenthood under the condition of mental disorders are needed. To date, within Germany there has been a lack of research evaluating the costs of mental health treatment and use of social services by children and adolescents with parents with mental illness. Methods As part of a multicentre randomised controlled trial, use and costs of health and social services were assessed for a sample of 332 children and adolescents with parents with mental illness in six regions of Germany. Service use at baseline was assessed by the German version of the Children and Adolescent Mental Health Service Receipt Inventory. Costs were calculated for 12 months based on diagnosis and service user status and described separately. Cost drivers were identified by means of a two-part regression model. Results Total mean costs for 12 months for the total sample amount of € 3736.35 (95% CI: € 2816.84-4813.83) per person. Children with a psychiatric diagnosis generated a total of € 5691.93 (95% CI: € 4146.27-7451.38) of costs per person, compared to € 1245.01 (95% CI: € 657.44-1871.49) for children without a psychiatric diagnosis. The logit part indicates significant odds ratios for individual functioning and diagnosis of the child as well as for family functioning. The linear part reveals that increasing individual functioning in the child is related to decreasing costs. Conclusions Children of families with parents with mental illness use a broad spectrum of mental health care, school-based support and youth welfare services even if they are not yet diagnosed as having a mental disorder. Further research should examine whether these institutions are sufficiently qualified and interlinked to meet the support needs of this vulnerable group. Trial registration The study was registered at the 07/10/2014 before the start of data collection (04/11/2014) at the German clinical trials register (Deutsches Register Klinischer Studien, DRKS, nr: DRKS00006806, https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00006806 ).